2023
DOI: 10.3390/coatings13020244
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Strength Parameters of Composite Cements as Affected by Storage Temperature—A Review of the Literature

Abstract: Fixed restorations are now among the most common restorations in modern dental prosthodontics. The current view in prosthodontics of maximum preparation economy is causing an increased interest in the mechanical properties of cements. Among the most important properties of materials used for indirect cementation are mechanical properties, i.e., hardness and compressive strength. These properties can change as a result of changes in physical factors. The purpose of this study was to analyze the available litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 67 publications
0
0
0
Order By: Relevance
“…Additionally, three studies reveal no statistically significant difference in microhardness values [5,10,30]. Moreover, six studies report both an increase in microhardness and fracture toughness [4,6,11,14,24,29]. Furthermore, one study indicates an increase in microhardness, but no statistically significant difference in fracture toughness [32].…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Additionally, three studies reveal no statistically significant difference in microhardness values [5,10,30]. Moreover, six studies report both an increase in microhardness and fracture toughness [4,6,11,14,24,29]. Furthermore, one study indicates an increase in microhardness, but no statistically significant difference in fracture toughness [32].…”
Section: Resultsmentioning
confidence: 91%
“…However, heating the composite resin results in an increase in microhardness at both the top and bottom surfaces, as elevated material temperature leads to more polymerization and hardening [36]. It is worth noting that some studies observed increased microhardness at temperatures ranging from 50°C to 60°C, while others showed either decreased or insignificant effects at different temperatures [6,9,16,22,24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations